2021
DOI: 10.1002/adfm.202100274
|View full text |Cite
|
Sign up to set email alerts
|

A Liquid Gripper Based on Phase Transitional Metallic Ferrofluid

Abstract: Magnetic fields enable dexterous, precise, and real‐time control of ferromagnetic materials. However, most materials, including glasses, organics, and metals, are nonmagnetic and often do not respond to a magnetic field. Here, a transitional ferrofluid (TF) made by embedding magnetic iron particles into pure gallium through the treatment of highly concentrated HCl solutions, as well as its switchable interlocking force to objects during the phase change, is introduced to achieve magnetic manipulation of non‐ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 28 publications
1
53
0
Order By: Relevance
“…Representative pictures of three kinds of machines (rigid machines, soft machines, transformable machines) and corresponding component materials as well as their approximate Young’s modulus. Reproduced with permission from ref . Copyright 2016 John Wiley and Sons.…”
Section: Introductionmentioning
confidence: 99%
“…Representative pictures of three kinds of machines (rigid machines, soft machines, transformable machines) and corresponding component materials as well as their approximate Young’s modulus. Reproduced with permission from ref . Copyright 2016 John Wiley and Sons.…”
Section: Introductionmentioning
confidence: 99%
“…711 A gallium-based iron NP ferrofluid, called transitional ferrofluid (TF), was made to provide switchable interlocking force during phase change to achieve magnetic manipulation of non-magnetic objects. 712 The transitional ferrofluid is a unique temperature-and magneto-responsive remote controlled liquid gripper which enables intimate contact with arbitrarily shaped objects, as illustrated in Fig. 45.…”
Section: Looking Back: Two Highly Successful Ferrofluid Applicationsmentioning
confidence: 99%
“…(c) The liquid TF droplet can easily transform its shape on a large scale and pass through narrow channels under control of the magnetic field; (d) when a strong magnetic field is applied at the bottom of the liquid TF, the transformable TF presents macroscopic protuberances immediately because of the formation of a chain-like alignment of iron particle; (e) the multi-thorn structure formed can bear more than 500 grams of weight; (f ) The artificial hand made by rubber and TF (I) can mimic the different gestures of a real hand such as "thumbs up (II)", "OK (III)" and grasping the fruit (IV) through melting TF, reshaping and solidifying. (g) Solidification of TF enables a strong adhesion force to glass and an interlocking force to the weight (500 g) (reproduced from ref 712. with permission from John Wiley and Sons, copyright 2021).…”
mentioning
confidence: 99%
“…Similarly, King et al 91 reported that the peak formation instability in an ionic liquid ferrofluid can be further exploited to act as an ionic liquid thruster, which is especially useful for space propulsion technology. Moreover, biomedical applications – including magnetically triggered drug delivery, 92 the hyperthermia treatment of cancer, 92 as contrast agents for magnetic resonance imaging, 92 the magneto-mechanical actuation of cell receptors and biosensors, 93 and as engineered platforms such as in soft robotics, 94–96 magnetically assembled photonic structures, and bioinspired arrays in combination with other curable materials – also involve magnetowetting as their building block. In essence, the wetting dynamics of the concerned FF droplets, namely, the contact line motion, contact angle change, or shape evolution, determine the performance of these applications.…”
Section: Magnetowetting Dynamicsmentioning
confidence: 99%
“…The recovery time and deformability ratio results observed for different liquid metal marbles highlight the potential of the proposed method in the domain of RF and metamaterials. Most recently, by embedding magnetic nanoparticles in the presence of highly concentrated HCl solutions into a previously non-magnetic metal such as gallium, a stable transitional ferrofluid (TF) was prepared by Wang et al 96 These TFs were later tested as a gripper in a magnetic field to transport non-metallic objects across a platform. The performance of the liquid gripper was intricately related to the initial phase transition of the TF during its heating and magnetization.…”
Section: Magnetowetting Dynamicsmentioning
confidence: 99%